The relationship between benefits of Record Management Filing System and the job performance among support staff of administrative at Kementerian Dalam Negeri, Koperasi dan Kepenggunaan / Nur Farhana Abdul Latif - Abdul Latif, Nur Farhana (2018)
Majority of the organizations today have implemented the record management filing system to shift from traditional way which keeps the record manually to be more systematic. Nevertheless, in managing the system in the organization, the employees must go through the condition of the technology and the efficiency of the system. The objective of this study was to determine the relationship between the condition of the technology saving time and the acceptance of efficiency of filing system towards job performance among the support staff. A monitor structured questionnaire was used at the main instrument and the data analyzed using the Statistical Package in the Social Science Software (SPSS) version 20.3. The researcher distributed 80 questionnaires to the support staff at Kementerian Perdagangan Dalam Negeri, Koperasi dan Kepenggunaan (KPDNKK) Kuching Sarawak, all staff was being responded to the questionnaire. The finding showed that there was a relationship between the condition of technology save time and the acceptance of efficiency system towards the job performance. The result of the study also showed that support staff major resulting was efficiency of the system have strong relationship with the job performance.